Customer Relationship Management As A Proposed Marketing Strategy: A Case Study Of Seafood Company In Bogor - Gracia Ulina Christanti Bawono; Atik Aprianingsih (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Indonesia’s fisheries and marine industry is a valuable sector and one that needs to be continuously developed. About 62% of Indonesia's territory is sea which has a very large potential wealth of marine resources, especially in the fisheries and marine products industry sector. The study narrows its scope to investigate the decline in sales at one seafood company based in Bogor, specifically within the business market segment. Employing qualitative methodology, the research analyses the personal selling process, identifying a potential link between declining salesperson performance and challenges in managing client relationships. Data from interviews and observations with clients, salespersons, and competitors form the basis for internal and external analyses, culminating in a SWOT analysis. The study reveals that while clients perceive personal selling positively, relationship management poses challenges. Additionally, technological opportunities from online systems are identified through PESTLE analysis. The research recommends a strategic shift towards utilizing online and integrated business operation systems, particularly in customer relationship management, to enhance salespersons' performance and address relationship management issues. The proposed strategy aims to optimize personal selling effectiveness.